Creation оf New Types оf Competitive Cutting Plates аnd Manufacture оf Pilot Instrument for Mechanical Processing of Hard-To-Machine Materials - Klymenko, S.A.; Prokopiv, M.M. (Science and Innovation, 2024)
Introduction and Problem Statement. The use of tools with cutting plates made of hard alloys and ceramics is a constant trend in the development of modern metalworking. Practical experience proves that it provides upgrading modes of cutting, reducing the idle time of equipment and the machine use per one detail. Taking into account the production output, it is important to improve the technologies of manufacturing such products with the requirements of environmental safety and the use of low cost technological components. Purpose. The aim of the research is to create a more environment friendly technology for the production of competitive cutting plates made of hard alloys and ceramics using low cost technological components. Materials and Methods. To prepare powders for sintering, a grinding method based on simultaneous shear and shock action, which enables to obtain a two-fractional composition of powder mixture with a narrow size range of spherical shape particles, has been improved. The application of PVA solution in alcohol as a plasticizer has enabled the production of plates with twice reduced content of dry residue of organic component, as compared with the rubber solution in gasoline, and to thrice reduce the duration of distillation in vacuum. Results. A batch of RNMN 120400T and SNMN 120412T cutting inserts has been manufactured. They have been tested while turning and milling the parts made of iron and steel. The tests have shown a 1.12-2.0 time increase in stability of cutting tools. Conclusion. An advanced environment safe technology for manufacturing highly wear-resistant cutting inserts from hard alloys and ceramics has been developed.